Engaging Science Teachers in Socioscientific Issue-Based Pedagogy in Indian Classrooms - Meenakshi Kaushik; Sugra Chunawala; Deepa Chari (Journal of Research in Environmental and Science Education, 2026)
The integration of Socioscientific Issues (SSIs) in science education has been widely recognised for its potential to enhance students’ scientific literacy and engagement with real-world issues. SSIs provide a framework for students to explore issues that intersect with science and technology (S&T), allowing them to develop critical thinking, problem-solving, and decision-making skills. However, despite growing policy support, teachers often face challenges in implementing SSI-based pedagogy due to its multidisciplinary nature, lack of training resources, and time constraints. This study explores a prototype short-term intervention program aimed at equipping secondary science teachers with the knowledge and skills necessary for effective SSI-based instruction. Grounded in the theoretical frameworks of co-construction and Pedagogical Content Knowledge (PCK), the intervention engaged two experienced science teachers in a structured process of developing and implementing SSI-based learning modules. Using a qualitative case study approach, data were collected through semi-structured interviews, recorded intervention sessions, teacher reflections, and module analyses. Findings indicate that while teachers recognised the value of SSIs in fostering student engagement and critical thinking, they encountered difficulties in balancing scientific content with social dimensions, managing value-laden discussions, and aligning SSI instruction with curricular demands. The study identifies key strategies and resources that facilitated teachers’ adaptation to SSI-based pedagogy, emphasising the role of reflective practices, contextualisation, and structured support in overcoming pedagogical challenges. By analysing teachers’ evolving PCK, this research contributes to the development of targeted professional development programs that bridge the gap between policy aspirations and classroom practices, ultimately promoting the integration of SSIs in science education.